A Model for an Emotional Respondent Robot - Sancar, Ayse E.; Sonmez, Elena Battini (Springer International Publishing Ag, 2018)
The aim of this study is to design an emotional regulation model based on facial expressions. It is argued that emotions serve a critical function in intelligent behavior and some researchers posed the questions of whether a robot could be intelligent without emotions. As a result, emotion recognition and adequate reaction are essential requirements for enhancing the quality of human robot interaction. This study proposes a computational model of emotion capable of clustering the perceived facial expression, and using cognitive reappraisal to switch its internal state so as to give a human-like reaction over the time. That is, the agent learns the person's facial expression by using Self Organizing Map, and gives it a meaning by mapping the perceived expression into its internal state diagram. As a result, the presented model implements empathy with the aim to enhance human-robot communication.
3rd International Symposium on Signal Processing and Intelligent Recognition Systems (SIRS) -- SEP 13-16, 2017 -- Manipal Univ, Manipal Inst Technol, Manipal, INDIA